Concentração de ácido hialurônico em pregas vocais de indivíduos jovens e idosos - Korn, Gustavo Polacow [UNIFESP] (2009)
Objective: to compare and evaluate hyaluronic acid (HA) concentration in the cover, vocal ligament, and vocal muscle of normal vocal folds, in young and elderly men and women. Method: A hyaluronic acid binding protein obtained from bovine nasal cartilage and determined by fluorometric assay was employed. ELISA plates coated with adsorbed binding protein were sequentially incubated with material samples from the middle portion of the cover, vocal ligament, and vocal muscle of 19 young subjects and 20 elderly ones, of both genders; biotin-conjugated binding protein; and streptavidin-europium conjugate. After europium release in an enhancement solution, final fluorescence was measured in a fluorometer. Results: Statistically significant comparisons: (1) Higher HA concentration in the cover and vocal ligament when compared to vocal muscle, in the whole sample; (2) Higher HA concentration in vocal ligament when compared to vocal muscle in young subjects of both genders, considering each group separately. Statistically non-significant data: (3) Higher HA concentration in vocal ligament when compared to the remaining portions; (4) Higher HA concentration in the cover of young women and lower concentration in vocal ligament when compared to young men; (5) HA value fall with aging, more prominent in the cover of women and in all portions of male subjects; (6) Lower HA concentration in elderly men, in all portions, keeping the difference between genders in the cover. Conclusion: From the hyaluronic acid concentration study in young and elderly subjects’ vocal fold we can conclude that there is a higher HA concentration in the cover and vocal ligament when compared to vocal muscle, in the whole sample; a higher HA concentration in vocal ligament when compared to vocal muscle in young subjects of both genders, considering each group separately.